A phase 2 trial of regorafenib as a single agent in patients with chemotherapy‐refractory, advanced, and metastatic biliary tract adenocarcinoma. Issue 6 (18th December 2018) - Sun, Weijing; Patel, Anuj; Normolle, Daniel; Patel, Krishna; Ohr, James; Lee, James J.; Bahary, Nathan; Chu, Edward; Streeter, Natalie; Drummond, Summer
Abstract : Background: Biliary tract cancers are rare, aggressive neoplasms. Most patients present with advanced/unresectable or metastatic disease at diagnosis, and no second‐line regimen has demonstrated clinical benefit. This was a phase 2 study evaluating the efficacy and safety of regorafenib in patients who had advanced/unresectable or metastatic disease after receiving standard therapy. Methods: In this single arm‐study, patients with advanced/unresectable or metastatic biliary tract cancer who failed at least 1 line of systemic chemotherapy received regorafenib once daily on a schedule of 21‐days on/7‐days off in a 28‐day cycle. Patients initially received a standard 160 mg dose. After toxicity assessments in the first 3 patients, the dose was reduced to 120 mg for subsequent patients, as preplanned. The primary endpoint was progression‐free survival (PFS). Secondary objectives included overall survival (OS), the objective response rate, and the disease control rate. Results: Forty‐three patients received at least 1 dose of regorafenib, and 34 patients who received at least 1 cycle of treatment were evaluable for tumor response. The median PFS was 15.6 weeks (90% confidence interval, 12.9‐24.7 weeks), and the median OS was 31.8 weeks (90% confidence interval, 13.3‐74.3 weeks), with survival rates 40% at 12 months and 32% at 18 months. A partial response was achieved in 5 patients (11%), and 19 had stable disease (44%), for a disease control rate of 56%. The toxicity profile was as expected, with grade 3 and 4 adverse events reported in 40% of patients. The most common toxicities were hypophosphatemia (40%), hyperbilirubinemia (26%), hypertension (23%), and hand‐foot skin reaction (7%). Conclusions: The current results suggest promising efficacy of regorafenib in patients with chemotherapy‐refractory, advanced/metastatic biliary tract cancer, warranting further studies to confirm its clinical efficacy. There is a clear unmet need for effective therapies in patients who have advanced and metastatic biliary tract cancer. Abstract : There is a clear unmet need for effective therapies in patients who have advanced and metastatic biliary tract cancer. The results from this phase 2 study provide encouraging data for the use of regorafenib as a single agent in patients with previously treated, advanced, unresectable, and metastatic biliary tract cancer.